2022
DOI: 10.1108/ecam-08-2022-0721
|View full text |Cite
|
Sign up to set email alerts
|

The co-movement effect of managers' psychological factors on the BIM adoption decision in SMEs: a study based on fsQCA

Abstract: PurposeGiven the complexity of building information modeling (BIM) adoption decisions in small- and medium-sized enterprises (SMEs) in the Architecture, Engineering and Construction (AEC) industry, understanding BIM adoption decision-making through the net effect of a single factor on BIM adoption decisions alone is limited. Therefore, this paper analyzed the co-movement effect of managers' psychological factors on the BIM adoption decisions from the perspective of managers' perceptions. The purpose is to let … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Firstly, the literature on BIM adoption has produced inconsistent findings regarding several vital relationships that influence BIM adoption intentions. For example, while some studies [10,19,20] have found performance expectancy to be a significant predictor of adoption intention, others [18,21] have reported it as non-significant. Similarly, Murguia et al [22] have identified effort expectancy as a significant predictor of BIM adoption intention, while Xue et al [10] have reported a non-significant relationship.…”
Section: Literature Review 21 Research Gap In Bim Adoption Literaturementioning
confidence: 99%
“…Firstly, the literature on BIM adoption has produced inconsistent findings regarding several vital relationships that influence BIM adoption intentions. For example, while some studies [10,19,20] have found performance expectancy to be a significant predictor of adoption intention, others [18,21] have reported it as non-significant. Similarly, Murguia et al [22] have identified effort expectancy as a significant predictor of BIM adoption intention, while Xue et al [10] have reported a non-significant relationship.…”
Section: Literature Review 21 Research Gap In Bim Adoption Literaturementioning
confidence: 99%